Features of ground beetle (Coleoptera, Carabidae) assemblages in areas of meadow biocenosis with and without Sosnovsky’s hogweed (Heracleum sosnowskyi) - Pliskevich, Elena S. (Experimental Biology and Biotechnology, 2020)
As a result of a study conducted in 2018, 41 species of ground beetles from 23 genera were identified in the Ushachsky District of the Vitebsk Region (Belarusian Lakeland) as a part of ground beetle assemblages of meadow biocenosis with clogging by the invasive Sosnovsky’s hogweed, whereas without clogging with hogweed 38 species from 21 genera were identified. Species Notiophilus biguttatus (Fabricius, 1779), Dyschiriodes globosus (Herbst, 1784), Bembidion quadrimaculatum (Linnaeus, 1761), Pterostichus oblongopunctatus (Fabricius, 1787), P. minor (Gyllenhal, 1827), P. nigrita (Paykull, 1790), Platynus assimilis (Paykull, 1790), P. krynickii (Sperk, 1835), Bradycellus caucasicus (Chaudoir, 1846), Ophonus laticollis (Mannerheim, 1825), Harpalus latus (Linnaeus, 1758), H. progrediens (Schauberger, 1922), Badister bullatus (Schrank, 1798) were recorded only in the biocenosis with clogging with hogweed. The species richness and the value of the biodiversity index of the ground beetle assemblages of the meadow biocenosis with clogging with hogweed were higher than these parameters of the ground beetle assemblages of the meadow biocenosis without hogweed. In the conditions of invasive hogweed thickets stratobionts boreholes dominated in the ground beetle assemblages (relative abundance 28.57 %), the participation of eurytopic (6 species, 20.37 %) and forest species (7 species, 12.01 %) was high, with a decrease in the share of participation meadow species (3 species, 1.37 %). For the biocenosis littered with hogweed, a high proportion of mesophiles (19 species, 52.44 %) was observed, against the background of a low proportion of mesogyrophils (9 species, 37.69 %).
Keywords: species richness; Belarusian Lakeland; stratobionts boreholes; eurytopic species; forest species